2007
DOI: 10.2172/920205
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical, Hydrogeologic and Vegetation Data Package for 200-UW-1 Waste Site Engineered Surface Barrier Design

Abstract: SummaryFluor Hanford (FH) is designing and assessing the performance of engineered barriers for final closure of U-plant waste sites. The ideal barrier will minimize recharge and plant intrusion into the underlying waste, thereby providing protection for human health and the environment. FH is using the Pacific Northwest National Laboratory (PNNL) Subsurface Transport over Multiple Phases (STOMP) simulator as the primary design optimization tool for simulating surface barrier performance. PNNL is supporting FH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 89 publications
(109 reference statements)
0
11
0
Order By: Relevance
“…Soil thermal properties also play a critical role in the water and energy balance. These properties were estimated using pedotransfer functions that take into account the mineralogy and water-retention relationships of the porous materials (Ward 2007). Some properties were also derived from literature values measured on Hanford sediments (Cass et al 1984;Shannon and Wilson 1994).…”
Section: Simulationsmentioning
confidence: 99%
“…Soil thermal properties also play a critical role in the water and energy balance. These properties were estimated using pedotransfer functions that take into account the mineralogy and water-retention relationships of the porous materials (Ward 2007). Some properties were also derived from literature values measured on Hanford sediments (Cass et al 1984;Shannon and Wilson 1994).…”
Section: Simulationsmentioning
confidence: 99%
“…Estimates of thermal conductivity and specific heat were based on Hanford Site values reported in the literature (Pruess 2000, Ward 2007. In this analysis, it was assumed that heat transfer was anisotropic because finer grained sediments underlay coarser grained sediments in the Ringold Formation.…”
Section: 7mentioning
confidence: 99%
“…Because no range of thermal parameters were reported in Pruess 2000 andWard 2007, and because initial simulations demonstrated that temperature predictions were not very sensitive to thermal parameter estimates for the Hanford and Ringold formations, a range of thermal parameters was not used. These input parameters, as well as selected hydraulic input parameters, are listed in Table 5.1.…”
Section: 7mentioning
confidence: 99%
“…Predicting infiltration requires consideration of unsaturated flow processes, precipitation, snow accumulation and melting, surface runoff, water storage, evaporation, transpiration, lateral diversion along sloped layers, and, ultimately, deep percolation (Ward and Gee, 1997;Ward and Keller, 2005). All of these processes occur in response to forcing meteorology that leads to temporal variability in air temperature, relative humidity, wind speed, and barometric pressure and, in the most sophisticated implementations, require the solution of coupled equations for mass and energy transport.…”
Section: Process Model Equationsmentioning
confidence: 99%